Melatonin influences reproduction in the sapphire devil Chrysiptera cyanea via regulation of dopamine 2b receptor transcription - Byun, Jun-Hwan; Mahardini, Angka; Rizky, Dinda; Udagawa, Shingo; Kodai, Fukunaga; Tan, Ee Suan; Kim, Jong-Myoung; Hur, Sung-Pyo; Takemura, Akihiro (Frontiers in Marine Science, 2024)
Melatonin and dopamine participate in the regulation of reproduction-related hormone/peptide synthesis and secretion at the hypothalamic–pituitary–gonadal axis in fish. Here, we report a unique reproduction-related interaction of melatonin and dopamine in the brain of the sapphire devil Chrysiptera cyanea, a tropical damselfish with a long-day preference. We examined the expression of arylalkylamine N-acetyltransferase 2 (aanat2)—a rate-limiting enzyme of melatonin, dopamine 2b receptor (d2b), gonadotropin-releasing hormone (gnrh1), and β-subunit of follicle-stimulating hormone (fshβ) and luteinizing hormone (lhβ)—in the brain of the sapphire devil. During the reproductive season, mature females were divided into the early vitellogenesis (EV), late vitellogenesis (LV), and post-spawning (PS) stages; a day-low and night-high profile of aanat2 was observed during EV and LV but not during PS. There were nocturnal increases in gnrh1 during EV and LV as well as d2b during LV, suggesting that melatonin has a positive effect on the levels of gnrh1 and d2b transcripts in mature fish. When the brains of females in the non-breeding season were sampled at 4-h intervals, nocturnal increases in the levels of fshβ and lhβ transcripts were observed at 00:00 and 04:00, respectively. The immersion of immature fish in melatonin-containing seawater for 6 h resulted in the upregulation of fshβ and lhβ, as well as downregulation of d2b, in the brain. Additionally, in situ hybridization analysis showed that melatonin treatment lowered the signals of d2b transcripts in the ventral hypothalamus, rostral pars distalis, proximal pars distalis, and pars intermedia, suggesting that melatonin has a negative impact on the levels of d2b transcripts in the hypothalamus and pituitary of immature females; the opposite effect is likely concerning the levels of fshβ and lhβ transcripts in the pituitary. In conclusion, melatonin positively and negatively acted on the hypothalamus and pituitary in the sapphire devil; these opposite effects were related to differences in gonadal development status.